Optimization of Data Administration Management through Mentoring and Training for Village Apparatus in the Statistics Love Village Program in Tanjung Pasir Village - Kalfin, Kalfin; Nugroho, Diyas Arya; Ramadhani, Sausan; Pradana, Reza Septian (Research Collaboration Community (RCC), 2025)
The Statistics Love Village Program helps improve the ability of village officials in efficiently managing potential village data. In Tanjung Pasir Village, limitations in administrative data processing have been an obstacle in data-based decision-making. Therefore, mentoring and training are needed to optimize data administration management. The aim of this activity is to optimize data administration management through mentoring and training for village officials in Tanjung Pasir Village through the Statistics Love Village Program. The Statistics Study Program and the Statistics Corner of Matana University collaborate with the Central Statistics Agency of Tangerang Regency in implementing this program. The results of this activity include mapping data on the number of aquaculture businesses and the total production volume of aquaculture. Based on the results of the activity, it can be concluded that the potential business sector in Tanjung Pasir Village is mainly engaged in milkfish farming, with most of the total aquaculture production being in brackish water. Based on the mapping of this potential data, it is hoped that village officials can make more targeted policies and improve community welfare.